Boundedness of Commutators of High-Dimensional Hausdorff Operators - Guilian Gao; Houyu Jia (Journal of Function Spaces and Applications)
We prove the boundedness of commutators of high-dimensional Hausdorff operators 𝐻Φ,𝑏 on Lebesgue space with central BMO function or Lipschitz function. Furthermore, the boundedness on Herz spaces and Morrey-Herz spaces is also obtained.